2003
DOI: 10.1093/ps/82.7.1061
|View full text |Cite
|
Sign up to set email alerts
|

Growth curves for body weight and major component parts, feed consumption, and mortality of male broiler chickens raised to maturity

Abstract: Body weight; yield of the major carcass component parts of breast, leg, thigh, drumstick, breast meat, thigh meat, and drumstick meat; feed consumption; feed conversion; and mortality of male broiler chickens from two commercial strains were measured from hatching to 154 d of age. As no differences were observed between the two strains, for any of the traits measured, the statistical analysis was made using pooled data. Growth curves for BW, breast weight, and leg weight were calculated. The Richards function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
41
2
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 32 publications
10
41
2
11
Order By: Relevance
“…reported that strain and sex can affect feed intake and feed conversion ratio. Goliomytis et al (2003) reported that feed intake was comparable between Cobb-500 and shaver Starbro strains through 154 days of age. They reported that feed intake of broilers increased until 84 days of age and then declined until 112 days of age.…”
Section: Feed Intakementioning
confidence: 93%
“…reported that strain and sex can affect feed intake and feed conversion ratio. Goliomytis et al (2003) reported that feed intake was comparable between Cobb-500 and shaver Starbro strains through 154 days of age. They reported that feed intake of broilers increased until 84 days of age and then declined until 112 days of age.…”
Section: Feed Intakementioning
confidence: 93%
“…This probably because the broilers in all giving methods, up to 35 days old, were still in very fast growth phase. Where according to Goliomytis et al (2003) maximum growth rate is achieved between the ages of 44 and 49 days. All these variables had similar pattern with the tendency that, eventhough statistically not different, the treatment of JB50-0 had slightly higher values compare to the others.…”
Section: Effect Of Treatment On the Performance Of Broilermentioning
confidence: 99%
“…Net gain, which takes into account both the feed and rearing costs, reached a maximum between 42 and 49 days of age, and then decreased (Baéza et al, 2011). The results of Goliomytis et al (2003) showed that live bodyweight was rapidly increasing until 44 days of age only, at which maximal growth rate was attained. Beyond this age, growth rate declined and approached zero at maturity.…”
Section: Introductionmentioning
confidence: 98%
“…However, the effects on profit, meat product quality, the environment, and animal welfare have been little investigated (Baéza et al, 2011). Goliomytis et al (2003) made a study to investigate the growth pattern of chickens beyond the common slaughter age of 42 days to maturity. Schmidt (2008) carried out a study in an integrated company to evaluate live and economic performance of broilers as a function of market age.…”
Section: Introductionmentioning
confidence: 99%